2015 IEEE 23rd International Conference on Program Comprehension 2015
DOI: 10.1109/icpc.2015.36
|View full text |Cite
|
Sign up to set email alerts
|

Eye Movements in Code Reading: Relaxing the Linear Order

Abstract: Code reading is an important skill in programming. Inspired by the linearity that people exhibit while natural language text reading, we designed local and global gaze-based measures to characterize linearity (left-to-right and top-to-bottom) in reading source code. Unlike natural language text, source code is executable and requires a specific reading approach. To validate these measures, we compared the eye movements of novice and expert programmers who were asked to read and comprehend short snippets of nat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
104
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 138 publications
(112 citation statements)
references
References 27 publications
7
104
1
Order By: Relevance
“…Moreover, software engineering researchers repeatedly found huge variations in productivity even between programmers with the same level of experience [5][6][7] . Several previous studies showed the psychological characteristics of expert programmers in their behaviors 8,9 , knowledge structures [10][11][12] , and eye movements [13][14][15][16] . Although these studies clearly illustrate the behavioral specificity of expert programmers, it remains unclear what neural bases differentiate expert programmers from novices.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, software engineering researchers repeatedly found huge variations in productivity even between programmers with the same level of experience [5][6][7] . Several previous studies showed the psychological characteristics of expert programmers in their behaviors 8,9 , knowledge structures [10][11][12] , and eye movements [13][14][15][16] . Although these studies clearly illustrate the behavioral specificity of expert programmers, it remains unclear what neural bases differentiate expert programmers from novices.…”
Section: Introductionmentioning
confidence: 99%
“…Another study [25] by the same group by authors extends the work and looks in the linearity of natural language text reading and how this linear order is not followed when reading source code. They look at both experts and novices and show that novices also exhibit a less linear order when they read source code compared to natural language text.…”
Section: Eye Tracking As Assessmentmentioning
confidence: 92%
“…Our a-posteriori repository mining approach assumes a top-to-bottom reading order of blocks and a left-toright reading order for individual lines. We know that developers "jump" in the code when reading a file, only focusing on what seems important to solve the task at hand (Busjahn et al 2015;Siegmund et al 2014). However, in order to understand small coherent logical units, such as micro-clones, developers must necessarily read in the control-flow-direction of the software -which is top-to-bottom, left-to-right.…”
Section: Internal Threatsmentioning
confidence: 99%